Polish pharmacy professionals' beliefs about homeopathic medicines - a survey. - Agnieszka Sałek; Katarzyna Karłowicz - Bodalska; Dominik Marciniak (Polish Pharmaceutical Society, 2023)
Introduction: Homeopathy is an alternative therapeutic metod based on the principle of similarity, which was developed by Samuel Hahnemann in the 18th century. This method involves administering substances that may produce symptoms similar to the patient's reported ailment, in high dilutions. Despite scientific evidence speaking against this method, homeopathic products are defined as medicines by European law and undergo a special, simplified authorization procedure. In Poland, patients can only purchase homeopathic medicinal products at a pharmacy. Therefore, the recommendation obtained there may influence whether the patient decides to use a homeopathic medicine or not. Materials and methods: The study aimed to analyse the attitude of Polish pharmacists and pharmacy technicians towards homeopathic medicines. An anonymous questionnaire was conducted among professional pharmacy staff to assess their knowledge, beliefs, and recommendations regarding homeopathic medicines. Between January and April 2023, 298 respondents - 279 pharmacists and 19 technicians - completed the survey. The collected responses were statistically analyzed using STATISTICA v. 13.3. Statistical significance was checked using Pearson's χ2 test of concordance, assuming a p-value ≤ 0.05 as the level of significance. PCA principal component analysis was used to assess global relationships between the key variables analyzed regardless of scale. The constructed PCA model was estimated using the NIPALS iterative algorithm. Results: Out of the 298 survey respondents, 285 worked in community pharmacies. More than two-thirds of the respondents had personal experience using homeopathic medicines, and about one-third of them recommended such medicines to their patients. The willingness to recommend homeopathic medicines correlated with the respondent's history of positive effects of homeopathic medicines. Homeopathic medicines were most often recommended by women and people over 50 years of age. More than half of the professional pharmacy staff considered homeopathic medicines to be ineffective and to show only a placebo effect. When asked which conditions they recommended homeopathic medicines for, pharmacists and technicians most often indicated cold and flu symptoms, painful teething, and bruises and hematomas. Conclusions: The results of the survey suggest that most members of the professional pharmacy staff do not recommend homeopathic medicines to their patients. The problem of evaluating preparations with no proven therapeutic effect as effective mainly affects women over 50 and respondents from small towns. It is worth deepening the following study in the future, focusing on these groups of respondents. The knowledge gained in this way will make it possible to assess the extent to which this group of workers relies on scientific evidence and whether they are aware of making decisions based only on their own beliefs.